Akta Kualiti Alam Sekeliling 1974 (Akta 127): peranan dan keberkesanan peraturan, perintah dan kaedah-kaedah di bawahnya - Shamsuddin Bin Suhor, (Fakulti Undang - Undang, 2003)

(untitled)
Environmental Quality Act 1974 is a sign of commitment of Malaysian towards nature. This Act is related to the prevention, abatement, control of pollution and enhancement of the environment. It also deals with the administration of the environment and towards the achievement of the national environmental policy. The Act provides specific provisions with respect to licences, prohibition and control of pollution, appeal, delegation of powers and to make regulations for with respect to any matters to the environment. The additional regulations are needed so as to provide a clearer picture and smooth implementation of the main Act. It helps the enforcement mechanism of the Act. However, the enforcement of the Act, its rules, regulations and orders are subjected to interpretation, the capabilities of enforcement officers, their expertise and human factors. Therefore the awareness and fully understanding of the existing subsidiary legislation as provided by the Act is crucial for implementation and enforcement purposes